THE USAGE OF RUNNING DICTATION METHOD TO IMPROVE THE STUDENTS’ WRITING ABILITY - Tiodora Silalahi; Yulia Pratiwi (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
Writing is the difficult skill to master that is why exercise regularly needed. The objective of this study is to know the usage of running dictation method improves the students’ writing descriptive text. This experimental research was carried out in MTs Mesra Pematangsiantar in the academic year of 2020/2021. The research design of this study is classroom action research with quantitative approach. The population of this study is all students grade eight at junior high school, they are 212 students were divided into six classes. And as a sample of this study consist of 30% from the population were VIII-1 as the experimental group and VIII-2 as the control group. Each group consist of 35 students. The experimental group was treated by usage Running Dictation Method, while the control group was treated by using Direct Instruction. The finding of this research are the score pre-test in control group are 1740 where the mean is 49,71 and in experimental group 1542 where the mean is 44,05. The mean score of different in control group is 15,77 and the t-test is 4,86 The standard deviation of the data in control group is 11,01 and the effect size in teaching writing descriptive text in control group is 1,43 It means that the students ability is low. The students’ score post-test in control group are 2292 where mean is 65,48 and in experimental group are 3023 where the mean is 86,37 The mean score of different in experimental group is 42,32 and t-test for experimental group is 5,88. The standard deviation of the data in experimental group is 14,41 and the effect size in experimental group is 2,93. It means that the students ability is high. The data analysis show the following findings: (1) Usage Running Dictation Method is more effective than Direct Instruction in teaching writing, (2) students with high creativity have better writing ability than those having low creativity, (3) there is an interaction between usage running dictation method and teamwork between students in teaching writing